119k views
3 votes
X^3-5x^2-2x+24 factorize

User Bui
by
6.0k points

2 Answers

6 votes

Answer:(x-2)(x-3)(x-4)

Explanation:

Use the rational root theorem to get started, then factor the remaining quadratic to find:

f(x)=x^3-5x^2-2x+24

f(2)=(2)^3-5(2)^2-2(2)+24

f(2)=0

i.e 2 is a root of f(x)

(x-2) is a factor

Now by dividing x^3-5x^2-2x+24by (x-2),

we get q(x)=x^2-7x+12

Since, q(x) is also a factor of x^3-5x^2-2x+24

Factorising x^2-7x+12

(x-4)(x-3)

So, all the factors of

x^3-5x^2-2x+24 are (x-4),(x-3) and (x-2)

User Vincent Beltman
by
5.3k points
4 votes

Answer:

(x + 2)(x − 3)(x − 4) = 0

Explanation:

User Fscheidl
by
5.6k points